TELAAH REVOLUSI MENTAL DAN PENDIDIKAN KARAKTER DALAM PEMBENTUKKAN SUMBER DAYA MANUSIA INDONESIA YANG PANDAI DAN BERAKHLAK MULIA - Muhammad Kristiawan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2015)
Mental revolution and character education have an important role to advance human civilization. Essentially, the mental revolution and character education were aimed at making learners’ smart and noble. If these goals are achieved, the human civilization will tend to be more advanced than before. Conversely, if both or one of those goals ruled out, it will appear the destruction of civilization. For Indonesia, to make the learners’ smart and have moral required mental effort revolution integrated with a comprehensive character education. Mental revolution and character education are two aspects related and mutually aligned. Both of these provide relatively solutions to establish smart and noble Indonesian human resources.Kata kunci: revolusi mental, pendidikan karakter, sumber daya manusia Indonesia yang pandai dan berakhlak mulia